Activity of the novel polo-like kinase 4 inhibitor CFI-400945 in pancreatic cancer patient-derived xenografts - Lohse, Ines (Oncotarget, 2016)
BACKGROUND: Polo-like kinase 4 PLK4 plays a key role in centriole replication. Hence PLK4 inhibition disrupts mitosis, and offers a novel approach to treating chromosomally unstable cancers, including pancreatic cancer. CFI-400945 is a first in class small molecule PLK4 inhibitor, currently undergoing early phase clinical trials. RESULTS: Treatment with CFI-400945 significantly reduced tumor growth and increased survival in four out of the six models tested. Consistent with PLK4 inhibition, we observed reduced expression of the proliferation marker Ki-67 associated with an increase in nuclear diameter during treatment with CFI-400945. Additionally, treatment with CFI-400945 resulted in a significant reduction of tumor-initiating cells. DISCUSSION: These results support the further investigation of PLK4 as a drug target in pancreatic cancer. METHODS: Sensitivity to CFI-400945 was tested in a series of six patient-derived pancreatic cancer xenografts, selected to represent the range of growth characteristics, genetic features, and hypoxia found in pancreatic cancer patients.